Penerapan Metode Pembelajaran Interaktif Dalam Meningkatkan Hasil Belajar Siswa Pada Pembelajaran PAI - Soleha Putri Nasution; Parianto Parianto; Nurhaizan Sembiring (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
Islamic Religious Education (PAI) plays an essential role in shaping students' character and moral conduct. Through PAI learning, students are expected not only to understand the cognitive aspects of Islamic knowledge but also to internalize spiritual and moral values in their daily lives. Therefore, the success of PAI learning is measured not only by academic achievement but also by changes in students' attitudes and behavior that reflect their religious understanding. This study employed a quantitative approach with a one-group pretest-posttest design. The research sample consisted of all 50 eighth-grade students, selected using a saturated sampling technique. Data were collected through learning achievement tests administered before and after the treatment, as well as through observation and documentation. The data were analyzed using a paired sample t-test with the assistance of SPSS version 20. Descriptive analysis of students' scores before the implementation of the interactive learning method showed that the average pretest score was 51.90. After the application of the interactive learning method, the average posttest score increased to 87.80. These findings indicate that the interactive learning method has a positive and significant effect on improving the learning outcomes of eighth-grade students in Islamic Religious Education at SMP IT Harapan Bangsa Tanjung Morawa. The increase in average scores from pretest to posttest confirms an improvement in students' understanding and mastery of the material following the implementation of the method